A COGNITIVE PROCESSING OF ENGLISH LOANWORDS IN INDONESIAN: ADAPTATION AND ADOPTION ANALYSIS - Cenderato Cenderato; Exnasia Retno Palupi Handayani; Yusi Kurniati (STKIP Persada Khatulistiwa Sintang, 2023)
The main purpose of this paper is to describe English loanwords in Indonesian. The study covers English loanwords from the process of adaptation and adoption. The data had been collected from some literations and the former researches. Adaptation occurs in the rules of the Indonesian language i.e. spelling rules, word structure, pronunciation, and sentence structure. Meawhile, Adoption is to pick up English words as Indonesian words original patterns. Through the methods, ILLs may easily learn indonesian language both writing and speaking. Spelling and Pronunciation adaptions consist of 275 words and Spelling adaptions without Pronunciation adaptions of 78 worrds. It means at most 353 words through adapation. In addition, English adaptation also occur in Indonesian language. It occurs by taking the same meaning, spelling, pronunciation of 42 words and while the other by the same meaning, spelling, different pronunciation is of 32 words.